2008
DOI: 10.1007/bf03345640
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-invasive dynamic tests in the diagnosis of Cushing’s syndrome

Abstract: Our findings demonstrate that LDDST had 100% sensitivity for the diagnosis of CS and that HDDST and stimulation tests with CRH or desmopressin may be very useful for confirmation of CS etiology when analyzed together or when more stringent cut-offs are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
6
22
0
1
Order By: Relevance
“…As reported in some studies (2,5,6,7,10,11,12,14), we found that LNSC levels were higher in CS; a threshold value above 5.24 ng/ml provided a good accuracy to detect endogenous hypercortisolism, and in particular to discover CD, the most common form. LNSC was able to differentiate CS patients from the control population, which included not only healthy subjects but also patients with suspected CS, and our proposed threshold value is consistent with other data reported in the literature and obtained with RIAs (5, 11, 23).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As reported in some studies (2,5,6,7,10,11,12,14), we found that LNSC levels were higher in CS; a threshold value above 5.24 ng/ml provided a good accuracy to detect endogenous hypercortisolism, and in particular to discover CD, the most common form. LNSC was able to differentiate CS patients from the control population, which included not only healthy subjects but also patients with suspected CS, and our proposed threshold value is consistent with other data reported in the literature and obtained with RIAs (5, 11, 23).…”
Section: Discussionsupporting
confidence: 77%
“…UFC collection and the 1 mg DST are simple, but neither is able to make a certain diagnosis of CS (15,20,21). The LNSC test, as proposed recently (5,6,7,10,11,12,14), is a reliable, noninvasive, stress-free, and low-cost procedure to diagnose CS. Moreover, elevation of LNSC levels might be the first abnormality to be checked in the follow-up after surgery (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with metabolic syndrome were excluded from the study when they had: 1) low levels of free and total testosterone associated with high concentrations of FSH and LH, characterizing andropause or primary gonadal insufficiency; 2) altered prolactin and/or TSH levels; and/or 3) Cushing's syndrome (that was excluded when plasma cortisol levels were lower than 1.8 µg/dL at 8.00 p.m. after the intake of 1.0 mg of dexamethasone at 11.00 p.m. on the previous day) (12).…”
Section: Methodsmentioning
confidence: 99%
“…Once an accurate urine collection is achieved, the sensitivity of UFC measurement is 45-71% when specificity is set at 100% (5). The 1 mg overnight dexamethasone suppression test (DST) and the 2 mg dexamethasone 2-day suppression test (low-dose DST (LDDST)) are simple and inexpensive; failure of normal suppression of SeC is a well-known biochemical screening test when CS is suspected, showing a sensitivity and specificity O95 and 80% respectively (3,6,7).…”
Section: Introductionmentioning
confidence: 99%